SKEPTISME PROFESIONAL SEBAGAI PEMODERASI PENGARUH KOMPLEKSITAS TUGAS DAN TEKANAN KETAATAN TERHADAP AUDIT JUDGMENT - Iriantika S, I Made Toni; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
The purpose of this study to obtain empirical evidence of the influence of the complexity of the task, the pressure obedience and professional skepticism ability to moderate the effect of task complexity and adherence pressure on audit judgment. This research was conducted at the Regional Public Accounting Firm Bali in 2016. The number of samples taken 43 auditors who are willing to participate in this study. The sample in this research was determined by purposive sampling method. This study uses analysis techniques Moderated Regression Analysis. According to the research found that the complexity of the task variable positive effect on audit judgment, variable pressure observance negative effect on audit judgment, professional skepticism variable able to moderate the effect of task complexity and adherence pressure on audit judgment with adjusted R2 of 50.5 percent.
Keywords: Professional Skepticism, Complexity Duty, Obedience Pressure, Audit Judgment